Diffusion and following isothermal desorption of impurity and matrix atoms out of sapphire and its melt - Katrich, N.P.; Budnikov, A.T.; Krivonogov, S.I.; Miroshnikov, Yu.P. (Functional Materials, 2006)
Isotermal desorption of impurity matrix atoms (as CO, CO₂, H₂, H₂O) out os sapphire bulk has been studied. A theoretical model has been proposed for diffusion mechanism of the atoms included in gas-vacancy complexes 2Vᶦ-Mᶦ (Mᶦ being an atom, Vᶦ, a neutral vacancy). According to the model, the gas-vacancy complexes are formed due to breaking to the surface thereof becomes desorbed while another one becomes recombined into molecules and then desorbed. The equations describing the deffusion and desorption have been derived. The diffusion and desorption parameters have been determined for the atoms and molecules.